Multiple comparisons of diversity indices invaded by Lantana camara - Qureshi,H. (2021)
Abstract Current study assessed the impact of Lantana camara invasion on native plant diversity in Pothohar region of Pakistan. The approach used for study was random samplings and comparisons of diversity indices [number of species (S), abundance (N), species richness (R), evenness (Jꞌ), Shannon diversity index (Hꞌ) and Simpson index of dominance (λ)] with two categorical factors i.e., invaded and non-invaded (control). Control plots harboured by an average of 1.74 more species/10m2. The control category was diverse (Hꞌ=2.56) than invaded category (Hꞌ=1.56). The higher value of species richness in control plots shows heterogeneous nature of communities and vice versa in invaded plots. At multivariate scale, ordination (nMDS) and ANOSIM showed significant magnitude of differences between invaded and control plots at all sites. The decrease in studied diversity indices in invaded over control sites indicated that plant communities become less productive due to Lantana invasion.